NIVELES DE INTEGRACIÓN SOCIOCULTURAL EN UN ÁREA NATURAL PROTEGIDA DE MÉXICO - Castañeda, Xochitl Salomé; Velasco Orozco, Juan Jesús; Ruiz-Torres, Mónica Elizama (Universidad de Costa Rica, 2021)
The objective of this research is to analyze, from the approach of social anthropology, the levels of sociocultural integration existing and its influence on the management of natural resources in a Protected Natural Area in Mexico. To achieve this, an ethnographic method was applied in a peasant community. Five levels of sociocultural integration were detected that allowed to understand the relationships and links between environmental and sociocultural conditions.